Missional theological curricula and institutions - Kruger P. du Preez; Hans J. Hendriks; Arend E. Carl (Verbum et Ecclesia, 2014)
The article argues in favour of an all-embracing missional framework for curriculum development for theological institutions. When the curriculum of a subject such as ecclesiologyhas a missional hermeneutic, it will naturally lead to missional congregations. The authors use issues raised by the Network for African Congregational Theology (NetACT) institutions and the decisions of the Third Lausanne Congress in Cape Town (2010) as reference points in this article. They argue for a broad understanding of the concept missional and are of the opinion that curricula that are integrative, normative, contextual and missional will lead to spiritual maturity and will result in a positive impact on church and society as a whole. The missio Deias the work of the Trinitarian God is seen as being Gods initiative. The incarnational modelof Jesus Christ forms the basis for a theology and missiology where humility, vulnerability and servanthood play a pivotal role in curricula. An appeal is made for holistic missions with a strong emphasis on social engagement and the inclusion of community development. The Holy Spirit is seen as the empowering presence of the missio Dei, and the role of pneumatologyin missional curriculum development is underscored. Theological institutes should becomeproclamation institutions. Curricula should be ecumenical by nature and should include reaching the unreached and unengaged people groups. Theological education by extension is presented as an alternative way of decent ralised theological education.Intradisciplinary and/or interdisciplinary implications: The article calls for theology to be done with a missional hermeneutic, both intradisciplinarily and interdisciplinarily. The article involves theology and education and calls for all disciplines dealing with community development to collaborate.